Patient Safety Based Knowledge Management SECI to Improve Nusrsing Students Competency - Harianto, Joanggi Wiriatarina; Nursalam, Nursalam; Dewi, Yulis Setiya (Universitas Airlangga, 2015)
Introduction: Patient safety is an important component of health services quality,andÂ basic principles of patient care. Nursing students also have a great potential to make an action that could endanger the patient, because hospital is one of student practice area. The purpose of this study was to improve the nursing students competency in patient safety by using knowledge management SECI approached. Method: The study used exploratory survey, and quasy experiment. The samples were some of nursing students of STIKes Muhammadiyah Samarinda who were on internship programme that selected using simple random sampling technique, in total of 54 students. This researchâs variables were the knowledge management SECI based-patient safety and nursing studentâs competency. The data were collected by using questionnaires and observation. The data were analyze by using Partial Least Square (PLS). Result: The result showed that there were significant influence the implementation of a model patient safety based knowledge management seci on increased competence nursing students. Discussion: Improved student competency in patient safety using SECI knowledge management was carried out in four phases, that is Socialization, Externalization, Combination, and Internalization. The result was a new knowledge related to patient safety that able to improve the studentâs competency..Keywords: Patient safety, Knowledge management, SECI, competency